Studi Terhadap Implementasi Metode Takrir Bagi Penghafal Al-qur'an - Burhanudin Ata Gusman; Nanik Rahmanti; Yusuf Hanafiah (STAI Terpadu Yogyakarta, 2021)
Memorizing the Qur'an for some people is a difficulty in itself because of the need for self-awareness, for that this takrir method is one of the efficient methods for novice memorizers to memorize the Qur'an. Therefore, it is necessary to apply the takrir method in memorizing the Qur'an because this method is an effort to improve, maintain memorization that has been memorized so that it can be remembered. The purpose of this article is to make it easier for someone who wants to memorize the Qur'an, besides that, so that the reading is correct, the memorization can be remembered in long-term memory so it is very appropriate for people who memorize the Qur'an. Based on the above background, the formulation of the problem can be taken, how to implement the takrir method in memorizing the Qur'an. This article uses a qualitative method with an analytical descriptive model. The content of the discussion is that the takrir method is repeating memorization that has been memorized or that has been deposited with the teacher on an ongoing basis and istiqomah. This is intended so that the memorization that is memorized is maintained. The takrir method is a method for repeating rote memorization, so this takrir method is very important to apply, because memorizing and maintaining memorization is a difficult activity and sometimes boredom occurs.